2017
DOI: 10.1007/s10620-017-4688-6
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Laparoscopic Radiofrequency Ablation Over Percutaneous Radiofrequency Ablation in Hepatocellular Carcinoma

Abstract: LRFA appears to be superior to PRFA in terms of survival. LRFA may help reduce mortality in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Laparoscopic-RFA (L-RFA) represents an alternative when P-RFA is not feasible and laparotomy is contraindicated or is too invasive. The specific indications for L-RFA are represented by: severe impairment of the coagulation tests, large tumors (but < 3.5 cm) or multiple lesions requiring repeated punctures, superficial lesions adjacent to visceral structures, deep-situated lesions with a very difficult or impossible percutaneous approach, shortterm recurrence of HCC following percutaneous loco-regional therapies [5][6][7]. For HCC patients unfit for surgery, the efficacy of L-RFA appeared to be superior to P-RFA in terms of survival in the study conducted by Eun et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic-RFA (L-RFA) represents an alternative when P-RFA is not feasible and laparotomy is contraindicated or is too invasive. The specific indications for L-RFA are represented by: severe impairment of the coagulation tests, large tumors (but < 3.5 cm) or multiple lesions requiring repeated punctures, superficial lesions adjacent to visceral structures, deep-situated lesions with a very difficult or impossible percutaneous approach, shortterm recurrence of HCC following percutaneous loco-regional therapies [5][6][7]. For HCC patients unfit for surgery, the efficacy of L-RFA appeared to be superior to P-RFA in terms of survival in the study conducted by Eun et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study comparing laparoscopic RFA to percutaneous RFA in Korea similarly showed an advantage to the laparoscopic approach for HCC 29 . Although the method of ablation (laparoscopic or percutaneous) was not a significant determinant of overall or recurrence‐free survival on multivariate analysis, it was a significant determinant of overall survival after propensity score matching was performed between the two groups 29 . Furthermore, laparoscopic RFA significantly reduced the hazards ratio for death and decreased intrahepatic and local recurrences 29 …”
Section: Discussionmentioning
confidence: 95%
“…The lesions were assessed one and eight weeks after PRFA by CT or MRI. We defined complete ablation as hypoattenuation of the target area and the surrounding liver parenchyma, which was confirmed by radiology[ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…PRFA therapy is effective for controlling local tumours with improved survival and is the current standard for early-stage HCC requiring ablative treatments[ 4 - 11 ]. Although studies have demonstrated the superiority of LRFA to PRFA for patient survival[ 12 ], LRFA is more invasive than PRFA with higher risks of complications and requires general anaesthesia[ 13 ]. When percutaneous ablation treatments cannot be used, HR is a suitable alternative for the treatment of small HCC[ 14 ].…”
Section: Introductionmentioning
confidence: 99%